A reactive scheduling and control framework for integration of renewable energy sources with a reformer-based fuel cell system and an energy storage device. (March 2020) - Pravin, P S; Misra, Shamik; Bhartiya, Sharad; Gudi, Ravindra D.
Highlights: Proposition of a reactive scheduling approach for combating uncertainty in renewable energysources Hierarchical decomposition of the scheduling and control tasks Control based integration of uncertain renewable energy sources with deterministic energygeneration and storage devices Reactive feedback in an MLD based rolling horizon framework for integration of multiple powersources Demonstration of the proposed approach on several scenarios in energy uncertainty, with andwithout reactive feedback Abstract: The main technological barrier in relying solely on renewable energy resources is that the sources such as wind and solar are highly intermittent in availability and result in uncertainty in demand satisfaction. This paper focuses on the integration of these uncertain renewable energy sources along with relatively deterministic energy sources such as reformer based fuel cell and battery. The power mix scenario between these multiple renewable energy sources along with the reformer based fuel cell system, coupled with an energy storage option is envisaged in this paper to ensure undisrupted power supply, to combat the possible intermittent nature of these renewable sources. An appropriate scheduling layer which provides a detailed plan of the optimum contribution of the various available power sources is considered over one week (7 days) duration. A model predictive control (MPC) scheme is deployed at the lower level control layer that receives a measurement of the possible fluctuations or uncertainties in the renewable power sources and maintains a smooth operation of the power generation system through appropriate decisions on generation via the reformer based fuel cell or by exploiting the battery storage, to ensure a delay-free delivery of power to the external load. During real-time operation of the plant, due to the uncertainties in the contribution from solar and wind sources, the power demanded from the fuel cell and the battery is varied accordingly by the MPC layer to meet the overall power demand. The performance of the designed MPC to maintain a smooth delivery of power in both the absence and presence of uncertainties in the renewable energy sources, with and without a reactive feedback between the scheduling and control layers, is illustrated using case studies.